Cellular Uplink Impairments in Vehicular Repeater Deployments - Martin Lerch; Philipp Svoboda; Josef Resch; Markus Rupp (IEEE Open Journal of Vehicular Technology)
Vehicular repeater systems improve the mobile coverage inside railroad cars by amplifying the signals received by a pick-up antenna on the roof and distributing the amplified signals inside the car. Uplink signals are received accordingly in the cars, amplified and transmitted via the roof antenna. At the same time, amplified noise is also transmitted. In uplink direction, this can lead to impairments of mobile communication in the entire cell. However, in vehicular repeater systems there are other sources of uplink interference that could be mistakenly be interpreted as additive noise. In addition to the influence of additive noise, in this paper we investigate the influence of inter-symbol interference due to direct propagation through the windows, interference due to passive intermodulation that can occur in the indoor antenna, and interference due to limited isolation between the indoor and outdoor antenna. We introduce a pathloss model for a vehicle repeater system. Based on this model, we investigate the influence of these different sources of interference on the uplink experimentally. Depending on the kind of interference, we conduct our investigations over different system parameters, such as the penetration loss of the windows, isolation between the indoor and outdoor antenna, and the gain settings of the repeater. The findings presented in this study provide valuable insights for network operators and researchers, facilitating the design of robust and efficient vehicular repeater systems that enhance connectivity and user experience in cellular wireless networks.